1989
DOI: 10.1128/mcb.9.2.851
|View full text |Cite
|
Sign up to set email alerts
|

Induction of beta-polymerase mRNA by DNA-damaging agents in Chinese hamster ovary cells.

Abstract: Studies of mammalian cells with DNA polymerase inhibitors have suggested that 3-polymerase has a role in DNA repair (1,3,13,18,24), and the in vitro activity of purified ,-polymerase points to an in vivo role in resynthesis of short gaps after damaged residues have been excised (4,9,15,19,21,22). Lesions produced by several DNA-damaging agents are repaired by single-base excision or short-gap excision followed by resynthesis to fill the gap (8). It is unknown whether regulation of P-polymerase gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(64 citation statements)
references
References 27 publications
3
60
1
Order By: Relevance
“…Our data are consistent with other studies showing no increase of Polb after X-ray exposure. 35,36 Studies employing microarray technology have also found that repair genes are not upregulated after ionizing radiation exposure. 24,37 It is interesting to consider that if the adaptive response to ionizing radiation requires transcriptional activation, induction of BER genes may not be involved in radioadaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with other studies showing no increase of Polb after X-ray exposure. 35,36 Studies employing microarray technology have also found that repair genes are not upregulated after ionizing radiation exposure. 24,37 It is interesting to consider that if the adaptive response to ionizing radiation requires transcriptional activation, induction of BER genes may not be involved in radioadaptation.…”
Section: Discussionmentioning
confidence: 99%
“…It is a monomeric protein of 335 amino acids (39 kDa) that lacks exonuclease activities and appears to be the least accurate of the eukaryotic DNA polymerases in vitro (Kunkel, 1985). In vivo, it is expressed at a constant low level throughout the cell cycle (Zmudzka et al, 1988) and is inducible by some genotoxic treatments (Fornace et al, 1989). The increased mutation frequency we observed for the BCR ± ABL transfected Ba/F3 cells urged us to compare the expression of Pol b between the untransfected control Ba/F3 cells and the p190-and p210-transfected Ba/F3 cells.…”
Section: Spontaneous Mutation Frequencies In Bcr ± Abl Transfected Bamentioning
confidence: 99%
“…The lack of specificity in the inducing signal urges caution, however. There are numerous damage-inducible transcripts in mammalian cells for which there is so far no apparent function: an example is DNA polymerase which is 'induced' in CHO cells by MNNG treatment (37) although the increased mRNA levels do not seem to be correlated with increased DNA polymerase activity. Indeed, unless the rate-limiting step for DNA repair is polymerization, increased DNA polymerase alone would be of little value.…”
Section: Self-destructionmentioning
confidence: 99%